Razvoj Slovenske matice od njenih začetkov do prve svetovne vojne - Mahnič, Joža (Jezik in slovstvo, 1998)
The Slovenska matica was foundes in 1864 as a cultural institution in charge of promoting Slovenian science - especially the humanistic - and literature. It was a precursor of the Slovenian Academy of Sciences and Arts. Its development from its beginings till World War one may be devided into three stages of different levels of quality: the period of conservative Old Slovenians, the period of the feethinking Fran Levec, and the period of the New-Illyrian Fran Ilešič. The first period is characterized by stagnation, the secind by impressive activities, and the third by average achivements.
Keywords: Slovenska matica; zgodovinski pregledi; 1864/1914